Novel gonadal characteristics in an aged bovine freemartin - Remnant, J.G.; Lea, Richard G.; Allen, Ceri E.; Huxley, J.N.; Robinson, Robert S.; Brower, A. (Elsevier, 2014)
The gonads from a five year old freemartin Holstein animal were subjected to morphological analysis and to immunohistochemistry using antibodies against developmental and functional markers. We demonstrate, for the first time, the retention of anti-mullerian hormone (AMH) producing intratubular cells (Sertoli cells) in the context of abundant steroidogenic interstitial cells, and structures consistent with clusters of luteal cells. This novel report describes the clinical, gross and histological findings accompanying this newly described gonadal immunophenotype, and its implication in the understanding of freemartin development.